Potential and Supportability of Forage in Majalengka Regency for Sheep Farming - Itang Purnama; Dini Widianingrum (Fakultas Pertanian Universitas Majalengka, 2025)
This study aims to identify the potential of forage production and analyze its carrying capacity for the development of sheep farming in Majalengka Regency. The study was conducted through the identification of dominant types of forage fodder, as well as measurement of forage biomass production per hectare of data obtained from secondary data available from the Central Bureau of Statistics (BPS) of Majalengka Regency. The method used is quantitative descriptive method and then the data obtained is analyzed to calculate the carrying capacity of the land based on the need for dry matter (BK) per sheep per year. The results showed that the Majalengka Regency area has a fairly high diversity of forage species, with the potential for forage biomass production reaching an average of 20-25 tons of fresh material/ha/year or equivalent to 4-5 tons of BK/ha/year. Assuming the consumption needs of sheep are around 1.5 kg BK/day, then each hectare of land can support around 7-9 sheep per year. This finding shows that Majalengka has the potential carrying capacity of natural forage and agricultural waste of rice and corn straw to support the sustainable development of sheep farming. Some sub-districts that fall into this category include Maja (3.35), Bantarujeg (3.13), Kertajati (2.43) and Majalengka (2.09). This high index value indicates that the region has great potential to become a center for sheep farming development, because feed is available in sufficient or even excess quantities. Sheep farming centers in 2024 still focus on areas including Sindang (2.44), Banjaran (2.20), Panyingkiran (1.88), Argapura (1.56), and Cigasong (1.36). The high LQ reflects that the livestock sector is one of the main focuses of the economy in the region despite the low feed carrying capacity. Optimizing forage utilization requires sustainable feed management such as the creation of a central feed warehouse located in two different places, namely in kertajati, Bantarujeg and maja for feed buffering in the central sheep cattle area so that it can be integrated with the smallholder farming system